Princess Sitt al-Sham (d. 616 AH/d. 1220 AD): A Study of Her Life and Achievements - Saleh, L.Dr. Hadar Salim (Sulaimani Journal for Humanities, 2026)
Set Sham is one of the most prominent princesses of the Ayyubid period, not only because she is the sister of Sultan Saladin al-Ayyubi, but also for the roles she played during her brother's reign, as well as her support for him on both moral and material levels. Set Sham was distinguished by her beauty and intelligence, in addition to her known nobility of character, which she adorned with her scientific, cultural, and social interests, through her love and passion for knowledge and learning, especially jurisprudence and hadith, until she became one of the most important Shafi'i scholars of that era, in addition to her interest and love for the poor and needy, where she was generous with charity, and made her house a refuge for everyone who sought help or needed it. Her social role was not limited to helping the poor and needy only, as she also engaged in charitable works that made her one of the most beloved princesses among the general public. She also built khanqahs to care for Sufis, such as the Khanqah al-Husaymiyyah, and she endowed them to be used for the purposes of knowledge and Sufism. In addition, she built schools, where she built a Shafi 'i school in the neighborhood of Al-Awina near Damascus, which is the Shafi 'i Khanqah of Al-Husaymiyyah (Al-Baraniya), because it is located outside the walls of Damascus. This school was one of the most important and largest schools, with the most jurists and the largest endowments. The second school she built was the Shamiya al-Jawniyyah School.